Teacher Skills in Developing Project Based Learning (PjBL) Learning Tools in Elementary Schools - Reka Sutama Yasa, I Gede; Nice Maylani Asril (Universitas Pendidikan Ganesha, 2023)
The low skill of teachers in compiling learning tools is caused byteachers are less capable in preparing innovative learning tools. This research aims to analyze teacher skills in compiling learning tools and teachers' obstacles in compiling Project Based Learning (PjBL) learning tools. The type of research used is quantitative descriptive. The population in this study was 15 teachers spread across elementary schools consisting of 7 class I teachers and 8 class IV teachers. This research uses a cluster sampling technique. The data collection methods used were observation and distributing questionnaires. Meanwhile, the data collection instruments used in this research were rating scales and questionnaires. Test the content validity of the instrument using the Gregory formula. The results of the instrument content validity test were 1.00, thus obtaining a very high level of validity. The results of this research indicate that teachers' skills in compiling Project Based Learning (PjBL) learning tools are in the low category and teachers' obstacles in compiling Project Based Learning (PjBL) learning tools are in the high category. Mapping teacher competency to develop PjBL learning tools in each school is very important to illustrate the quality of teachers in compiling PjBL learning tools.